Pemanfaatan Sistem Informasi Geografis (Sig) Dalam Evaluasi Kesesuaian Pemanfaatan Ruang Dengan Rencana Tata Ruang Wilayah - Andi Chairul Achsan (Jurusan Teknik Arsitektur, Fakultas Teknik Universitas Tadulako Kampus Bumi Tadulako Tondo Jl. Sukarno-Hatta Km.9, Palu 94118 e-mail :Jurusan Arsitektur, Fakultas Teknik Universitas Tadulako Kampus Bumi Tadulako Tondo Jl. Sukarno-Hatta Km.9, Palu 941, 2013)
A method that can map information about spatial use and plan is needed to measure the suitable rate of spatial use and spatial plan. One of the methods that can be employed to evaluate their suitable rate was geographic information systems (GIS). In this method, spatial use can be identified, and deep analysis can be established to compare the suitability between spatial use and spatial plan. The evaluation started from confirming information about spatial use through GIS method by obtaining existing satellite image data processing, followed by overlaying or coorporating map of existing spatial use with map of spatial plan area. By doing this, the suitable rate of spatial use and spatial plan can be established.